Pengaruh Kualitas Layanan Akademik terhadap Kepuasan dan Loyalitas Mahasiswa di Kota Batam - Tanjung, Rona; Muliadi Manalu, Ferry; Tibrani, Tibrani; Asmarazisa Azis, Dhenny; Veronica Siagian, Sarah (Bahtera Inovasi, 2023)
The presence of computer technology with its process power has enabled the development of information systems in various fields. Although in some cases academic information systems for tertiary institutions have many benefits, there are still some weaknesses in the application of academic information systems, one of which is the lack of quality of management of the academic information system in supporting the work efficiency of academic procedures and user satisfaction. The purpose of this research is to see how the information system management model has an impact on user and organizational satisfaction so that the expected benefits are the development of research models that can assist higher education institutions in improving their academic information systems. The population in this study were students at tertiary institutions in Batam City. The sampling technique used is simple random sampling. Furthermore, the data analysis used is the Partial Least Square (PLS) approach. PLS is a component-based or variant-based Structural Equation Modeling (SEM) model where the variables used are system quality, information quality, service quality, user satisfaction, loyalty.